2012
DOI: 10.1002/ange.201201572
|View full text |Cite
|
Sign up to set email alerts
|

Direkte elektrophile N‐Trifluormethylierung von Azolen mit einem hypervalenten Iodreagens

Abstract: Die Bedeutung fluorierter Moleküle in der Chemie hat in den letzten Jahren rasch zugenommen. Der Anteil an aktiven Inhaltsstoffen mit mindestens einem Fluoratom liegt bei 30-40 % bei neu zugelassenen Pflanzenschutzmitteln und bei fast 20 % bei Medikamenten. Darüber hinaus bestand die Hälfte der zehn meistverkauften rezeptpflichtigen Arzneimittel des Jahres 2005 aus fluorierten Molekülen. [1] Eine ausgedehnte Datenbanksuche hat allerdings gezeigt, dass weniger als zehn N-trifluormethylierte Verbindungen beim Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 49 publications
0
11
0
3
Order By: Relevance
“…As shown in Scheme 1, the single crystal X-ray analysis of compound 5 revealed that the thiocyanate-group was S-bound to the oxygen atom of 2 rather than to the iodine. [11,12] Intrigued by this result, we conducted a brief comparison of the 1 H NMR spectra of the benziodoxoles and 2-iodobenzyl alcohol-derivatives that are shown in Figure 2. We found that the two compound classes (closed benziodoxole vs. open benzyl alcohol) generally display different characteristic signals in the aromatic region.…”
mentioning
confidence: 97%
“…As shown in Scheme 1, the single crystal X-ray analysis of compound 5 revealed that the thiocyanate-group was S-bound to the oxygen atom of 2 rather than to the iodine. [11,12] Intrigued by this result, we conducted a brief comparison of the 1 H NMR spectra of the benziodoxoles and 2-iodobenzyl alcohol-derivatives that are shown in Figure 2. We found that the two compound classes (closed benziodoxole vs. open benzyl alcohol) generally display different characteristic signals in the aromatic region.…”
mentioning
confidence: 97%
“…Heterocycles with electron-donating groups afford higher yields of N-trifluoromethylated products. [85] This can be explained by the fact that electron-poor groups lead to slower reactions allowing formation of side products. Indazoles are preferentially trifluoromethylated at the N-2 position.…”
Section: Trifluoromethylation Of N-centersmentioning
confidence: 99%
“…Diese Funktionalisierungs-/Fluorierungssequenz wurde auch für N-Perfluoralkyldithiocarbamate [493] und N-Heteroaryldithiocarbamate beschrieben (Schema 126). [489] Des Weiteren gehen primäre Phosphane mit dem Togni-Reagens II eine P-Trifluormethylierung ein. [459] Das von Umemoto beschriebene, thermisch instabile Reagens 6.1 ist das gleiche wie für die O-Trifluormethylierung von Phenolen.…”
Section: Synthese Von Trifluormethylaminenunclassified
“…B. Aniline, Pyridin und Azole, gelingen die Trifluormethylierung und die Isolierung der Produkte. [459,489] Zu den wichtigsten Synthesemethoden für Trifluormethylamine gehçren die nucleophile Fluorierung von Thiocar-bonyl-funktionalisierten Aminen und die N-Trifluormethylierung von Aminen. Die Amine werden zunächst als Thiuramidsulfide (Schema 124) [107c] ), [107c, 490] N-Alkyldithiocarbamate (Schema 125) [491] oder Formamide [458,492] derivatisiert und danach nucleophil fluoriert.…”
Section: Synthese Von Trifluormethylaminenunclassified
See 1 more Smart Citation